Micro-Place Disorder, Subjective Powerlessness and Violent Youth Group Involvement: Testing an Integrative Control Theory - Pauwels, Lieven J.R.; Svensson, Robert (International Journal of Criminology and Sociology, 2014)
In this study we test an integrative theory that seeks to explain why youth that live in disordered micro-places have an increase likelihood of becoming involved in a violent youth group. The emerging integrative theory is based on the principle of conceptual end-to-end integration and is the result of an attempt to integrate (1) a contemporary version of subjective powerlessness theory with (2) an integrative control framework of violent youth group involvement. We submit the thesis that the both aforementioned models are highly suitable for conceptual integration as micro-place disorder is a common antecedent. In addition, both models share an intervening mechanism in the observed micro-place disorder- violent youth group involvement relationship: the concept of normlessness. An integrative model allows for the study of multiple pathways through which micro-place disorder and subjective powerlessness affect the likelihood of becoming involved in a violent youth group. Using path analyses for continuous and dichotomous outcomes we test key propositions of our theoretical elaboration. Our research is based on a large sample of youths in early adolescence (N=2,486) in the urban context of Antwerp, the second largest city of Belgium. The results indicate that micro-place disorder increases decreases parental monitoring and increases feelings of subjective powerlessness. Normlessness and low self-control are important mediators in the “causal chain” between micro-place disorder, subjective powerlessness and violent youth group involvement. Low self-control and lifestyle risk further mediate the effects of subjective powerlessness, normlessness and micro-place disorder. The implications of these findings for future studies of violent youth group involvement are discussed.